Mountain Peaks of Nepal Himalaya (Journal of Tourism and Himalayan Adventures, 2021)
Nepal is a mountainous country with numerous peaks and pinnacles. It is shaped by tectonic movement, the action of gravity, and erosion. It is a gradual transition process from plain to mountain terrain. The present study explores the peaks of the Nepal Himalaya and visualizes the peaks as open sources for mountaineering. The height of Nepal Himalaya is derived from 'Nepal Himalaya Inventory' Gurung (1994), 'Inventory of Nepal Himalaya' (CDG, 2002), and 'Spot Height Shapefile' (DOS, 1998). The total number of peaks opened and mountaineering royalty are derived from the Department of Tourism. The spot height and administrative boundary are derived from the Department of Survey (DOS, 1998 & 2020). Shapefiles and Google Earth are used to map the distribution of the Himalayan peaks of Nepal, and the height categories are based on mountaineering royalty reports. This study also discusses some essential aspects of royalty generation and seeks a better understanding in exploring and identifying peaks for further mountaineering activities.